Sustainability, sustainable supply chain management - Horváth, Adrienn; Károlyi, László (International Journal of Engineering and Management Sciences, 2019)
With the rapid development of the world economy, the growing scarcity of natural resources and the degradation caused by pollution, environmental protection has become a major concern for countries and regions of the world. Sustainability is a common subject in many parts of the world and the various research areas among policy makers, journalists, scientists, universities and social debate. It is generally accepted, that companies also play an important role in addressing the challenges of sustainable development. In this role, making a key challenge to balance often conflicting pressures caused by sustainable development, that is, the level of corporate economic performance against environmental deterioration and social disruption. Effective integration of sustainability principles into companies requires action beyond the borders of organizations. The issue of sustainability is becoming more and more prominent in corporate governance. One of the most important area of supply chain management is for companies to gain a competitive edge in the market. This has a significant impact on the natural environment, and there is a growing need to integrate environmental thinking in supply chain management and processes, which is why companies are increasingly focusing on sustainable development, taking on more CSR initiatives and achieving a greener supply chain. Sustainable and green supply chain management practices have been developed over the past decades, trying to integrate environmental considerations into organizations by reducing unwanted negative consequences for the environment of production and consumption processes. In this article, I have examined the issues of sustainability and sustainable supply chain management, mainly based on descriptive secondary literature.